Morphological characterization of six Lombok upland rice cultivars - Baiq Sri Hartina; Rani Agustina Wulandari; Panjisakti Basunanda (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2021)
Lombok upland rice is one of the cultivars that have the potential as a genetic source. However, Lombok upland rice is almost rarely found. Therefore, conservation was carried out through morphological characterization to provide genetic information. This study aimed to describe the characteristics of six Lombok upland rice cultivars, namely, Reket Putek Bulu, Reket Putek Buntung, Reket Bireng Bulu, Reket Bireng Buntung, Pare Beaq Sapit, and Beaq Ganggas. A completely randomized design was used, consisting of these six Lombok upland rice cultivars as treatments. Two superior cultivars were also used for comparison. The study revealed sufficient divergence for various qualitative and quantitative traits. Pare Beaq Sapit and Beaq Ganggas shared common morphological characters, and both were tall plants. The auricle and ligule colors of Reket Bireng Bulu were different from those of the other cultivars. Reket Putek Buntung had the latest flowering and harvesting age. Reket Putek Bulu and Reket Bireng Buntung had a high number of productive tillers. Six cultivars of Lombok upland rice were characterized to have morphological diversity, so that they are expected to be used as genetic material in rice plant breeding, thereby developed to avoid extinction.